A Religiously Pluralistic Milieu in Austria during the Interwar Period: Results from an Oral History Project on the Constructions of Religious Plurality at Viennese Schools - Lehmann, Karsten (Journal of religion in Europe, 2023)
The article focuses on what the author describes as a religiously pluralistic milieu. It proposes that religious plurality is very much part and parcel of the recollections of the interwar period in Vienna, Austria. First, the article underlines the significance of sociocultural milieus, family upbringing, and school interaction for the constructions of religious plurality. Second, it raises the question of the social embeddedness of religious plurality in the memories of the interwar period in Vienna. The findings are based upon an oral history project, “Religiöse Vielfalt an Wiener Schulen der Zwischenkriegszeit” (ZwieKrie) (Religious plurality in Viennese schools during the interwar period). The project analyzed individual memories of religious plurality by a set of twenty-four contemporary witnesses attending Viennese schools during the 1920s and 1930s.